Factors affecting barriers of communication at Giga Wise Network Sdn Bhd / Siti Mariam Rahmat - Rahmat, Siti Mariam (2013)
Business communication is the sending and receiving of verbal and non verbal messages within the organizational context (Roebuck, 2001; Ober, 2001). To success in business, communication is one of the important key player to make sure the business success or failure. In any communication process, as necessarily have a barriers of communication to deliver successful information to the receiver. in developing effective communication, there is barriers happen between both sender and receiver within the communication process. Based on the previous study, there are elements of communication barriers that tend to develop the barriers of communication among sender and receiver. This research paper evaluates the factor affecting barriers of communication at Giga Wise Network Sdn Bhd. The study was conducted on November 2013 at Giga Wise Sdn Bhd located in Shah Alam by using primary and secondary data with 7 respondents of the employees, some observation towards the situation and issues in the organization and supported with previous study and related books and articles.